2023
DOI: 10.1186/s12957-023-03234-z
|View full text |Cite|
|
Sign up to set email alerts
|

Clinicopathologic and mutational profiles of primary breast diffuse large B cell lymphoma in a male patient: case report and literature review

Fengbo Huang,
Yachao Ruan,
Xiaojuan He
et al.

Abstract: Introduction Primary breast lymphoma (PBL) is rare, and most cases occur in female patients, with few reported cases in male patients. The clinical presentation is similar to that of breast cancer, but the condition needs to be well understood, as treatment options and clinical course vary. Hence, we provide a relatively rare case of primary breast diffuse large B cell lymphoma (PB-DLBCL) in a male, including its complete clinicopathological features, radiological findings, genomic mutational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the author reported that affiliation 5 should be corrected from…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author reported that affiliation 5 should be corrected from…”
mentioning
confidence: 99%